2022
DOI: 10.3390/cancers14225474
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the DNA Methylation Landscape of TFF1/TFF2 in Gastric Cancer

Abstract: As one of the most frequently occurring tumor types, the increasing incidence of gastric cancer (GC) has been observed in the past decades. The recent studies have illustrated that epigenetic modifications mediated by DNA methyltransferases (DNMTs) are the major epigenetic hallmark in GC progression. Nowadays, DNA methylation was considered to be necessary for inducing the silence of tumor suppressor genes (TSGs). As an important group of peptides, the TFF family has been confirmed to function as a TSG in vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Multiple reports indicate that TFF1 expression is downregulated by the EBV infection of AGS or MKN7 gastric cells [54][55][56]. TFF1 mRNA levels were similarly reduced in non-TCGA cohort-based EBVaGC samples compared to their EBVnGC counterparts [57]. Using the differential gene expression tool for EBV-GCR, a similar, statistically significant downregulation of TFF1 expression was also observed in the TCGA bulk sequencing data (Figure 6A).…”
Section: Example Case Studysupporting
confidence: 65%
See 1 more Smart Citation
“…Multiple reports indicate that TFF1 expression is downregulated by the EBV infection of AGS or MKN7 gastric cells [54][55][56]. TFF1 mRNA levels were similarly reduced in non-TCGA cohort-based EBVaGC samples compared to their EBVnGC counterparts [57]. Using the differential gene expression tool for EBV-GCR, a similar, statistically significant downregulation of TFF1 expression was also observed in the TCGA bulk sequencing data (Figure 6A).…”
Section: Example Case Studysupporting
confidence: 65%
“…Using the differential gene expression tool for EBV-GCR, a similar, statistically significant downregulation of TFF1 expression was also observed in the TCGA bulk sequencing data (Figure 6A). Both cell culture infection models and non-TCGA cohort EBVaGC data have identified increased methylation of the TFF1 gene in the presence of EBV [54,57]. The methylation and silencing can be reversed by 5-aza−2 -deoxycytidine treatment in culture, suggesting that EBV-induced hypermethylation is important for this repression [54].…”
Section: Example Case Studymentioning
confidence: 99%
“…TFF1 was first identified in the MCF-7 breast cancer cell line, and its full gene sequence was subsequently cloned [66]. Since then, numerous studies have found abnormal expression of TFF family proteins (mainly TFF1 and TFF3) in various solid tumors [67][68][69]. Research has shown that TFF2 is associated with energy metabolism and can regulate skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Ge et al reported that MUC1 is associated with the methylation of trefoil factor family 2 (TFF2), a secreted peptide that promotes epithelial repair, in Helicobacter pylori-infected gastric cells [55]. However, the mechanism through which this occurs is yet to be elucidated [57]. Furthermore, aberrant MUC1, following H. pylori infection regulates the methylation status of TFF2, thus contributing to the silencing of this peptide, leading towards GC development [57].…”
Section: Gastric Adenocarcinomamentioning
confidence: 99%
“…However, the mechanism through which this occurs is yet to be elucidated [57]. Furthermore, aberrant MUC1, following H. pylori infection regulates the methylation status of TFF2, thus contributing to the silencing of this peptide, leading towards GC development [57]. A further study by Shi et al identified that the methylation of the promoter region in the MUC6 gene leads to the downregulation of MUC6 expression, which may promote the metastasis of GC [58].…”
Section: Gastric Adenocarcinomamentioning
confidence: 99%